Impact of India's Free Trade Agreement with ASEAN on its goods exports: A gravity model analysis - Priyanka Khati; Chanwahn Kim (Economies, 2023)
The relationship between India and ASEAN has emerged as a crucial basis of their foreign policy. Both the regions signed a Free Trade Agreement in 2009, which came into effect in 2010. They are now reviewing the FTA to further enhance their economic cooperation. At this critical juncture, this study aimed to analyze the trade and export relationship between India and ASEAN and examine the extent to which the AIFTA effectively influenced it. Additionally, the study intended to determine what other factors influenced the trade and export relationship between the two regions and what future changes are needed in order to make this partnership mutually beneficial. To fulfill this objective, a gravity model was applied to a panel data from 2000-2019. A random effect model was utilized for the estimation. The empirical analysis concludes that the adoption of the AIFTA increased trade significantly; however, had no significant impact on raising exports. The study has identified rising NTMs as one of the important variables impeding realization of India's export potential to ASEAN. This study suggests that in order to increase India's exports and for the future of the FTA, India needs to emphasize on building stronger and extensive relationships with those countries in the ASEAN that are witnessing a higher GDP growth rate, such as Cambodia, Malaysia, the Philippines and Vietnam.
Keywords: 330; AIFTA; ASEAN; gravity model; India; non-tariff measures